Analysis of shear-wave splitting using multicomponent seismic data - Prajapati, S. (Society of Exploration Geophysicists, 2015)
The focus of this study is on shear wave splitting caused by preferential fractures and differential stress. Multicomponentmultisource offshore seismic data events recorded by arrays of three-component (3C) digital seismometers of Malay Basin provides valuable insight into the use of shear-wave splitting (SWS) measurements. The properties of shear wave splitting can be used to infer (1) the directional dependence of polarization (Ã¸) in fractures medium, usually parallel to crack orientation; and (2) the measurement of delay time (Î´t) between the two split S-waves is proponational to the number of cracks per unit volume with splitting uncertainties. Â© 2015 SEG.